Decadal Changes in Ventilation and Anthropogenic Carbon in the Nordic Seas. Issue 3 (15th March 2023) - Jeansson, Emil; Tanhua, Toste; Olsen, Are; Smethie, William M.; Rajasakaren, Balamuralli; Ólafsdóttir, Sólveig R.; Ólafsson, Jón
Abstract: We evaluate the decadal evolution of ventilation and anthropogenic carbon (Cant ) in the Nordic Seas between 1982 and the 2010s. Ventilation changes on decadal timescale are identified by evaluating decadal changes in mean ages and apparent oxygen utilization in each of the four main basins of the Nordic Seas (the Greenland and Iceland Seas, and the Norwegian and Lofoten Basins). The ages are derived from the transient time distribution approach, based on the transient tracers chlorofluorocarbon‐12 (CFC‐12) and sulfur hexafluoride (SF6 ). The different decades show different phases in ventilation, with the 2000s being overall better ventilated than the 1990s in all basins. For the Greenland Sea, we also show that the 2010s are better ventilated than the 2000s, with a clear shift in hydrographic properties. The evolution of concentrations and inventory of Cant is linked to the ventilation state. The deep waters get progressively older over the analyzed period, which is connected to the increased fraction of deep water from the Arctic Ocean. Plain Language Summary: The ocean region between Greenland, Iceland, and Norway, called the Nordic Seas, is a main site of deep‐water formation. This process produces dense waters and brings surface waters to larger depths, thereby ventilating the water below. This transports, among other things, man‐made CO2 (anthropogenic carbon; Cant ) and oxygen from the atmosphere into the interior ocean, thereby reducing the amount of CO2 stored in the atmosphere. This study investigates how the ventilation has changed in the Nordic Seas from 1982 to the 2010s. We find that the ventilation has changed with time, from a rather well‐ventilated state in 1982, to a reduced ventilation in the 1990s, and then a restrengthened ventilation from the 2000s. Key Points: Decadal means of mean age, apparent oxygen utilization, and anthropogenic carbon in the Nordic Seas main basins are presented Upper and intermediate waters better ventilated from the 2000s, while deep waters get older with time Clear link between ventilation status and inventory of anthropogenic carbon